PENYERAHAN PEKERJAAN KEPADA PIHAK KETIGA (OUTSOURCHING) DALAM BIDANG JASA BATU BARA DAN AKIBAT HUKUMNYA (STUDI DI PT. EPISI SUCOFINDO) - Sunariyo sinariyo (Universitas 17 Agustus 1945 Samarinda, 2014)
Abstract Labor conditions were relatively stable in the three decades of the New Order regime, the system of labor laws Indonesia shocked by the transformation suddenly of a model law Labour